PENGELOLAAN PROGRAM KEGIATAN IBADAH DI MADRASAH ALIYAH NEGERI BINTAN - Mukti, Wiji Aziiz Hari; Ni’mah, Ulfatun; Firman, Arham Junaidi; Utama, Esen Pramudya; Sugianto, Sugianto; Asvio, Nova (UIN Imam Bonjol Padang, 2023)
This study intends to describe the management of the worship program at MAN Bintan. This study used a purposive qualitative design at MAN Bintan which was held from January to April 2022. The Madrasah Head, Deputy Head of Student Affairs, Religious Teachers were sources of data acquisition. Overall data was collected through observation techniques at MAN Bintan, interviews with data sources, and documentation related to research activities. The validity of the data was tested through triangulation techniques. Data analysis was performed using the Miles and Huberman models. The results of the study show that the management of the congregational prayer and sunnah dhuha worship program at MAN Bintan has been well managed. This can be seen from its implementation which is mandatory for all students, teachers and staff. Although there are still students and teachers who do not participate in implementing it. In practice, students are given supervision by using attendance and worship control books. This attendance and worship control book will be checked every Friday morning and will eventually be included in the student report card grades of MAN Bintan